Precising of the vertebral body geometry by using Bézier curves - Tješová, Mária; Minárová, Mária (Proceedings of the Conference Algoritmy, 2016)
The biomechanical investigation of the human spine requires first of all the proper geometry of the focused object. The paper deals with a geometrical model developing of the human lumbar vertebral body by using B\'ezier curves - the tool for the curves creation of demanded shape and properties. The background theory and algorithm for the B\'ezier curves and their compound generation are introduced, the resulting geometry and the corresponding biomechanical computation results are performed.